The antonym for the word thrive would be A. Fail Hope this helps :)
Answer:
123 is not a multiple of 9, while all others are
99 is a multiple of 11, while all others are not
Answer: Where is the rest of the question?
Step-by-step explanation:
![x = \frac{ 419 }{ 113 } ~,~y = -\frac{ 208 }{ 113 } ~,~z = \frac{ 21 }{ 113 }](https://tex.z-dn.net/?f=x%20%3D%20%5Cfrac%7B%20419%20%7D%7B%20113%20%7D%20~%2C~y%20%3D%20-%5Cfrac%7B%20208%20%7D%7B%20113%20%7D%20~%2C~z%20%3D%20%5Cfrac%7B%2021%20%7D%7B%20113%20%7D)
<h2>
Explanation:</h2>
We have the following system of three linear equations:
![\begin{array}{ cccc }2~ x&+~~4~ y&+~~32~ z&~=~6\\5~ x&+~~8~ y&+~~~~ z&~=~4\\4~ x&+~~5~ y&+~~2~ z&~=~6\end{array}](https://tex.z-dn.net/?f=%5Cbegin%7Barray%7D%7B%20cccc%20%7D2~%20x%26%2B~~4~%20y%26%2B~~32~%20z%26~%3D~6%5C%5C5~%20x%26%2B~~8~%20y%26%2B~~~~%20z%26~%3D~4%5C%5C4~%20x%26%2B~~5~%20y%26%2B~~2~%20z%26~%3D~6%5Cend%7Barray%7D)
Let's use elimination method in order to get the solution of this system of equation, so let's solve this step by step.
Step 1: Multiply first equation by
and add the result to the second equation. So we get:
![\begin{array}{ cccc }2~ x&+~~4~ y&+~~32~ z&~=~6\\&-~~~2~ y&-~~~79~ z&~=~-11\\4~ x&+~~5~ y&+~~2~ z&~=~6\end{array}](https://tex.z-dn.net/?f=%5Cbegin%7Barray%7D%7B%20cccc%20%7D2~%20x%26%2B~~4~%20y%26%2B~~32~%20z%26~%3D~6%5C%5C%26-~~~2~%20y%26-~~~79~%20z%26~%3D~-11%5C%5C4~%20x%26%2B~~5~%20y%26%2B~~2~%20z%26~%3D~6%5Cend%7Barray%7D)
Step 2: Multiply first equation by −2 and add the result to the third equation. So we get:
![\begin{array}{ cccc }2~ x&+~~4~ y&+~~32~ z&~=~6\\&-~~~2~ y&-~~~79~ z&~=~-11\\&-~~~3~ y&-~~~62~ z&~=~-6\end{array}](https://tex.z-dn.net/?f=%5Cbegin%7Barray%7D%7B%20cccc%20%7D2~%20x%26%2B~~4~%20y%26%2B~~32~%20z%26~%3D~6%5C%5C%26-~~~2~%20y%26-~~~79~%20z%26~%3D~-11%5C%5C%26-~~~3~%20y%26-~~~62~%20z%26~%3D~-6%5Cend%7Barray%7D)
Step 3: Multiply second equation by −32 and add the result to the third equation. So we get:
![\begin{array}{ cccc }2~ x&+~~4~ y&+~~32~ z&~=~6\\&-~~~2~ y&-~~~79~ z&~=~-11\\&&+~~\frac{ 113 }{ 2 }~ z&~=~\frac{ 21 }{ 2 }\end{array}](https://tex.z-dn.net/?f=%5Cbegin%7Barray%7D%7B%20cccc%20%7D2~%20x%26%2B~~4~%20y%26%2B~~32~%20z%26~%3D~6%5C%5C%26-~~~2~%20y%26-~~~79~%20z%26~%3D~-11%5C%5C%26%26%2B~~%5Cfrac%7B%20113%20%7D%7B%202%20%7D~%20z%26~%3D~%5Cfrac%7B%2021%20%7D%7B%202%20%7D%5Cend%7Barray%7D)
Step 4: solve for z.
![\begin{aligned} \frac{ 113 }{ 2 } ~ z & = \frac{ 21 }{ 2 } \\ z & = \frac{ 21 }{ 113 } \end{aligned}](https://tex.z-dn.net/?f=%5Cbegin%7Baligned%7D%20%20%20%20%20%20%09%5Cfrac%7B%20113%20%7D%7B%202%20%7D%20~%20z%20%26%20%3D%20%5Cfrac%7B%2021%20%7D%7B%202%20%7D%20%5C%5C%20%20%20%20%20%20z%20%26%20%3D%20%5Cfrac%7B%2021%20%7D%7B%20113%20%7D%20%20%20%20%20%20%09%5Cend%7Baligned%7D)
Step 5: solve for y.
![\begin{aligned}-2y-79z &= -11\\-2y-79\cdot \frac{ 21 }{ 113 } &= -11\\y &= -\frac{ 208 }{ 113 } \end{aligned}](https://tex.z-dn.net/?f=%5Cbegin%7Baligned%7D-2y-79z%20%26%3D%20-11%5C%5C-2y-79%5Ccdot%20%5Cfrac%7B%2021%20%7D%7B%20113%20%7D%20%26%3D%20-11%5C%5Cy%20%26%3D%20-%5Cfrac%7B%20208%20%7D%7B%20113%20%7D%20%5Cend%7Baligned%7D)
Step 6: solve for x by substituting
and
into the first equation:
![2x+4(-\frac{208}{113})+32(\frac{21}{113})=6 \\ \\ 2x-\frac{832}{113}+\frac{672}{113}=6 \\ \\ 2x=6+\frac{832}{113}-\frac{672}{113} \\ \\ 2x=\frac{838}{113} \\ \\ x=\frac{319}{113}](https://tex.z-dn.net/?f=2x%2B4%28-%5Cfrac%7B208%7D%7B113%7D%29%2B32%28%5Cfrac%7B21%7D%7B113%7D%29%3D6%20%5C%5C%20%5C%5C%202x-%5Cfrac%7B832%7D%7B113%7D%2B%5Cfrac%7B672%7D%7B113%7D%3D6%20%5C%5C%20%5C%5C%202x%3D6%2B%5Cfrac%7B832%7D%7B113%7D-%5Cfrac%7B672%7D%7B113%7D%20%5C%5C%20%5C%5C%202x%3D%5Cfrac%7B838%7D%7B113%7D%20%5C%5C%20%5C%5C%20x%3D%5Cfrac%7B319%7D%7B113%7D)
Finally:
![x = \frac{ 419 }{ 113 } ~,~y = -\frac{ 208 }{ 113 } ~,~z = \frac{ 21 }{ 113 }](https://tex.z-dn.net/?f=x%20%3D%20%5Cfrac%7B%20419%20%7D%7B%20113%20%7D%20~%2C~y%20%3D%20-%5Cfrac%7B%20208%20%7D%7B%20113%20%7D%20~%2C~z%20%3D%20%5Cfrac%7B%2021%20%7D%7B%20113%20%7D)
<h2>Learn more:</h2>
Solving System of Equations: brainly.com/question/13121177
#LearnWithBrainly
Answer:
See the explanation bellow
Step-by-step explanation:
Given data
We are told that Mary earns $7.25 an hour
The function for her salary is s = 7.25h
<em>s is a function of h because h is the time, and s a dependent variable on the time, the longer she works the more money she makes</em>